1970
DOI: 10.3329/bjsir.v43i4.2236
|View full text |Cite
|
Sign up to set email alerts
|

Chromium(VI) Reducing Native Microorganisms for Remediation of Chromium Eco-toxicity in Environment of Bangladesh

Abstract: Feeds and fertilizer production from tanned skin-cut wastes is the most direct phenomenon of chromium eco-toxicity leading to food chain contamination in Bangladesh. Tanning industries of Hazaribagh at Dhaka process some 220 t of hide per day with release of 600-1000 Kg tanned skin-cut waste (SCW) per ton processed hide. The SCW is protein-rich and unscientifically used to produce poultry and fish feeds, and organic fertilizer. A huge migration of chromium can happen into poultry products, fish and vegetables,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1970
1970
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Bacterial cells might initially need to adjust to the chromium toxicity before initiating its reduction reaction until the growth was increased to reduce chromium with more efficiency. Similar observation was reported by Rafiqullqh et al, who showed that chromium tolerant Staphylococcus aureus and Pediococcus pentosaceus, reduced 100% hexavalent chromium within 24 hours 21 .…”
Section: Discussionsupporting
confidence: 89%
“…Bacterial cells might initially need to adjust to the chromium toxicity before initiating its reduction reaction until the growth was increased to reduce chromium with more efficiency. Similar observation was reported by Rafiqullqh et al, who showed that chromium tolerant Staphylococcus aureus and Pediococcus pentosaceus, reduced 100% hexavalent chromium within 24 hours 21 .…”
Section: Discussionsupporting
confidence: 89%
“…Due to its high oxidation potential, it can easily penetrate biological membranes and cause health hazards (Chaudhary et al 2003). Feeds and fertilizer production from tanned skin-cut wastes (SCW) is the most direct phenomenon of chromium ecotoxicity leading to food chain contamination in Bangladesh (Rafiqullah et al 2008). The SCW is protein-rich and indiscriminately used to produce poultry and fish feeds, and organic fertilizer.…”
Section: Introductionmentioning
confidence: 99%
“…It causes health hazards since it can easily enter biological cell membranes (Ogale et al, 2003). Tanned skin-cut wastes (SCW) which are used to produce feeds and fertilizers, are the direct phenomenon of chromium toxicity (Rafiqullah et al, 2008).…”
mentioning
confidence: 99%